KOORDINASI ANTAR-LEMBAGA PEMERINTAH DAN EFEKTIVITAS KEBIJAKAN KESEJAHTERAAN - Widjaja, Gunawan; Dhanudibroto, Handojo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the relationship between inter-agency coordination and the effectiveness of welfare policies through a literature review. Inter-agency coordination is a crucial factor in enhancing synergy, efficiency, and accountability in the implementation of social welfare programmes, thereby minimising duplication and waste of resources. This study examines various literature discussing coordination mechanisms, challenges faced, and their impact on aid distribution and the achievement of social welfare objectives. The results of the study indicate that effective coordination is supported by intensive communication, data integration, visionary leadership, and harmonious regulations. However, obstacles such as differences in interests among institutions, limited resources, and inaccuracy in targeting remain major challenges. This study recommends strengthening the coordination system, improving human resource capacity, and utilising information technology as key strategies to enhance the effectiveness of welfare policies. Thus, solid inter-agency coordination is an important foundation for achieving inclusive, sustainable, and widely impactful welfare policies for society.